Classes of Utility Functions Admitting Tyrni's Homogeneous Saving Function - Kalman, P. J. (Review of Economic Studies, 1969)
Journal Article Classes of Utility Functions Admitting Tyrni's Homogeneous Saving Function Get access P. J. Kalman P. J. Kalman State University of New York at Stony Brook Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 36, Issue 1, January 1969, Pages 122–124, https://doi.org/10.2307/2296350 Published: 01 January 1969 Article history Received: 15 January 1968 Revision received: 24 June 1968 Published: 01 January 1969